2019
DOI: 10.1111/cod.13224
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant contact‐allergic reactions to iodopropynyl butylcarbamate and iodine

Abstract: Background: Iodopropynyl butylcarbamate (IPBC) is a broad-spectrum preservative for use in several product types, including cosmetics, in which its concentrations have been limited by EU legislation because of concerns related to its iodine content and release, and the risk of subsequent iodine overdose.Objectives: To report on concomitant patch test reactions observed with iodine and IPBC in patients sensitized to iodine-containing antiseptics.Patients: Between 2012 and 2018, seven patients, six from Belgium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…However, other studies found a lower sensitization prevalence (eg, 0.53%) 57 . IPBC liberates iodine, which has also been supported by observing simultaneous contact allergy to IPBC and iodine 58 . Owing to possible endocrine interference, use concentrations are restricted to between 0.02% in rinse‐off products and 0.0075% in deodorants/antiperspirants for many years (SCCNFP/0826/04, EU Cosmetics Regulation, Annex V/56).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, other studies found a lower sensitization prevalence (eg, 0.53%) 57 . IPBC liberates iodine, which has also been supported by observing simultaneous contact allergy to IPBC and iodine 58 . Owing to possible endocrine interference, use concentrations are restricted to between 0.02% in rinse‐off products and 0.0075% in deodorants/antiperspirants for many years (SCCNFP/0826/04, EU Cosmetics Regulation, Annex V/56).…”
Section: Discussionmentioning
confidence: 93%
“…57 IPBC liberates iodine, which has also been supported by observing simultaneous contact allergy to IPBC and iodine. 58 Owing to possible endocrine interference, use concentrations are restricted to between 0.02% in rinse-off products and 0.0075% in deodorants/antiperspirants for many years (SCCNFP/0826/04, EU Cosmetics Regulation, Annex V/56). It would be of interest to further investigate IPBC regarding the clinical relevance of (weak) positive patch test reactions.…”
Section: Additional Consecutively Tested Allergensmentioning
confidence: 99%
“…In the case of iodopropynyl butylcarbamate (IPBC), it is iodine liberation and systemic availability that led the EU to limit the use concentration to 0.02% in rinse-off, 0.01% in leave-on cosmetics and 0.0075% in deodorants, see (EC) No 1223/2009. The recent observation of frequent concomitant allergic reactions to IPBC and iodine [340] supports this cautionary approach, pointing to a relevant co-exposure to both IPBC, which is a contact allergen in its own right [341], and (liberated) iodine.…”
Section: Allergen-specific Aspectsmentioning
confidence: 99%
“…1223/2009. Der aktuelle Bericht über häufige konkomitante allergische Reaktionen auf IPBC und Iod [340] untermauert diesen vorsichtigen Ansatz und deutet auf eine relevante Koexposition gegenüber IPBC als eigenständigem Kontaktallergen [341] und (freigesetztem) Iod hin.…”
Section: Diskussionunclassified